Oligomerization of Mutant p53 R273H is not Required for Gain-of-Function Chromatin Associated Activities - Annor, George K.; Elshabassy, Nour; Lundine, Devon; Conde, Don-Gerard; Xiao, Gu; Ellison, Viola; Bargonetti, Jill (Frontiers in Cell and Developmental Biology, 2021)
The TP53 gene is often mutated in cancer, with missense mutations found in the central DNA binding domain, and less often in the C-terminal oligomerization domain (OD). These types of mutations are found in patients with the rare inherited cancer predisposition disorder called Li-Fraumeni syndrome. We previously found that mutant p53 (mtp53) R273H associates with replicating DNA and promotes the chromatin association of replication-associated proteins mini-chromosome maintenance 2 (MCM2), and poly ADP-ribose polymerase 1(PARP1). Herein, we created dual mutants in order to test if the oligomerization state of mtp53 R273H played a role in chromatin binding oncogenic gain-of-function (GOF) activities. We used site-directed mutagenesis to introduce point mutations in the OD in wild-type p53 (wtp53), and mtp53 R273H expressing plasmids. The glutaraldehyde crosslinking assay revealed that both wtp53 and mtp53 R273H formed predominantly tetramers, while the single OD mutant A347D, and the dual mtp53 R273H-A347D, formed predominantly dimers. The R337C, L344P, mtp53 R273H-R337C, and mtp53 R273H-L344P proteins formed predominantly monomers. Wtp53 was able to activate the cyclin-dependent kinase gene p21/waf and the p53 feedback regulator MDM2. As expected, the transactivation activity was lost for all the single mutants, as well as the mtp53 R273H-dual mutants. Importantly, mtp53 R273H and the dual oligomerization mutants, R273H-A347D, R273H-R337C, and R273H-L344P were able to interact with chromatin. Additionally, the dual oligomerization mutants, R273H-A347D, R273H-R337C, and R273H-L344P, maintained strong interactions with MCM2 and PARP1. Our findings suggest that while mtp53 R273H can form tetramers, tetramer formation is not required for the GOF associated chromatin interactions.